JMJD6 orchestrates a transcriptional program in favor of endocrine resistance in ER+ breast cancer cells - Das, Partha; Gupta, Aritra; Desai, Kartiki V. (Frontiers in Endocrinology, 2022)
High expression of Jumonji domain containing protein 6 (JMJD6) is strongly associated with poor prognosis in estrogen receptor positive (ER+) breast cancer. We overexpressed JMJD6 in MCF7 cells (JOE cells) and performed RNA-seq analysis. 76% of differentially expressed genes (DEGs) overlapped with ER target genes. Pathway analysis revealed that JMJD6 upregulated a larger subset of genes related to cell proliferation as compared to ER. Interestingly, JOE cells showed a decrease in ER target gene expression prompting us to check ER levels. Indeed, JOE cells showed a significant decrease in both ESR1 and ER levels and JMJD6 siRNA transfection increased the expression of both. Additionally, JOE cells showed increased RET and ERK1 expression, events associated with resistance to endocrine therapy. Accordingly, JOE cells displayed lower sensitivity and survived better at higher doses of 4-hydroxy tamoxifen (Tam) as compared to parental MCF-7 cells. Conversely, LTED-I and TAM R that resist Tam induced death, showed high expression of JMJD6. Further, JMJD6 siRNA treatment decreased growth and improved Tam sensitivity in TAM R. Comparison of JOE DEGs with known Tam signature genes showed a substantial overlap. Overall, these data suggest that blocking ER alone in patients may not eradicate proliferation of JMJD6 expressing ER+ cells and JMJD6 may predispose and sustain endocrine therapy resistance. We propose that immunostaining for JMJD6 could be developed as a potential marker for predicting endocrine therapy resistance. Further, antagonizing JMJD6 action in women expressing higher amounts of this protein, may offer a greater clinical benefit than endocrine therapy.